Normocomplementemic urticarial vasculitis: An unusual presentation - Robin George Manappallil; Bhargavan Pallivalappil; Abhay Mani Martin; Neena Mampilly; Apurva Rao (Wolters Kluwer Medknow Publications, 2020)
Urticarial vasculitis (UV) is a form of cutaneous vasculitis which lasts for >24 h. Clinically, the patients present with erythema and wheals. The level of complement decides the type of UV. This is a case of a middle-aged lady, who developed vesiculobullous lesion over her leg after trekking. She was diagnosed to have normocomplementemic UV. Bullous presentation of UV is a rare scenario.